1983
DOI: 10.1007/bf02553343
|View full text |Cite
|
Sign up to set email alerts
|

Colonic obstruction secondary to impaction of a large calcified fecolith

Abstract: The case of a patient with colonic obstruction secondary to impaction of a large calcified fecolith is presented. Clinical features, radiographic findings and treatment are described and the literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…74,75 Retrospective analysis revealed a 5-to 6-times increased risk of fecal impaction resulting from chronic constipation. 68,70,71 (6) Bowel perforation and stercoral peritonitis: Extremely impacted feces (fecaloma) can compress the colonic wall, causing an ischemic ulcer 76 and subsequent perforation, 77,78 culminating in stercoral peritonitis 78,79 and sometimes death.…”
mentioning
confidence: 99%
“…74,75 Retrospective analysis revealed a 5-to 6-times increased risk of fecal impaction resulting from chronic constipation. 68,70,71 (6) Bowel perforation and stercoral peritonitis: Extremely impacted feces (fecaloma) can compress the colonic wall, causing an ischemic ulcer 76 and subsequent perforation, 77,78 culminating in stercoral peritonitis 78,79 and sometimes death.…”
mentioning
confidence: 99%
“…4 Some cases of fecalith have been reported as being caused by intestinal stasis. [5][6][7] We know that a patient who has been on dialysis for 20 years is likely to develop gastrointestinal amyloidosis. It has been reported that paralytic ileus, gastrointestinal bleeding, and perforation by ischemic colitis are serious clinical symptoms in dialysis patients who have gastrointestinal amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…A calcified faecolith has a well‐delineated appearance on plain films 2 . A calcified faecolith is present in 10% of inflamed appendices and may also be seen in Meckel’s diverticula 3 . On barium enema examination, faecaloma shows as a bulky intraluminal mass with no attachment to the colonic mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…2 A calcified faecolith is present in 10% of inflamed appendices and may also be seen in Meckel's diverticula. 3 On barium enema examination, faecaloma shows as a bulky intraluminal mass with no attachment to the colonic mucosa. Its large size, mobility and evidence of barium around its margins are some of the signs that differentiate it from a tumour.…”
Section: Discussionmentioning
confidence: 99%